Examining Muslim’s Boycott Behaviour toward Online Gambling Products: The Roles of Religious Beliefs, Product Judgment, and Digital Marketing Interactions - Rivaldi Arissaputra; Maisa Azizah Asmara; Tias Eka Saputra (SAFE-Network, 2026)
This study examines Muslim consumers’ boycott behaviour toward online gambling products by integrating religious beliefs, product judgment, and digital marketing interactions within a structural model. Although online gambling is explicitly prohibited in Islamic teachings, its prevalence in Indonesia continues to increase, indicating a gap between religious values and actual consumer behaviour. Using a quantitative approach, data were collected from 310 Muslim respondents in West Java through an online survey and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that religious beliefs and product judgment have a significant positive effect on boycott behaviour. Furthermore, digital marketing interactions play a significant mediating role in the relationships between religious beliefs and boycott behaviour, as well as between product judgment and boycott behaviour. These findings indicate that exposure to digital marketing content does not merely influence acceptance of online gambling but can also intensify consumer resistance when the product conflicts with moral and religious values. This study contributes to the literature on Muslim consumer behaviour by highlighting the interaction between moral values, cognitive evaluation, and digital marketing dynamics in shaping boycott decisions toward prohibited products.